Method for separating CH4 / N2 through high-vacuum calcination of multi-MOF mixed matrix membrane

By treating the polymetallic organic frame material with high vacuum calcination and mixing it with alkaline polymer, an efficient polymetallic organic frame mixed matrix membrane was prepared, which solved the application limitations of metallic organic frame materials in CH4/N2 separation and achieved excellent gas separation performance.

CN119633624AActive Publication Date: 2025-03-18TIANJIN POLYTECHNIC UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411806861.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The uneven carbonization of metal organic framework materials during vacuum resistance calcination is poorly compatible with the polymer matrix, which limits its application in CH4/N2 separation.

Method used

The polymetallic organic frame material was treated with high vacuum calcination technology to form surface carbonized hardened ZIF-8, MOF-74-Ni and UiO-66-NH2 nanoparticles, and mixed them uniformly with alkaline polymer polyvinylamine to prepare a polymetallic organic frame mixed matrix membrane by scraping the film method.

Benefits of technology

It significantly improves the separation performance of CH4/N2, achieves excellent CH4 permeability and selectivity, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633624A_ABST
    Figure CN119633624A_ABST
Patent Text Reader

Abstract

The invention relates to a method for separating CH4 / N2 through high-vacuum calcination of a multi-MOF mixed matrix membrane, aims to realize effective separation of methane and nitrogen, comprises a preparation method, and belongs to the technical field of membrane separation. According to the method, a vacuum resistance calcination technology is adopted, so that the separation performance of CH4 / N2 is remarkably improved. According to the invention, alkaline polymer polyvinylamine is uniformly mixed with SCH-M / SCH-Z and SCH-M / SCH-U, and the multi-metal organic framework mixed matrix membrane is prepared by adopting a membrane scraping method. The preparation method has the beneficial effects that the MOF is carbonized by fully utilizing high-vacuum resistance calcination, so that the influence of gas separation performance of MMMs due to poor compatibility of non-uniform carbonization and a polymer matrix is solved. The method is simple to operate, mild in condition and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of membrane separation, and specifically relates to a method for separating CH4 / N2 by high vacuum calcining multi-MOF mixed matrix membrane. Background Art

[0002] With the increasing demand for energy, it is essential to seek new clean energy that is environmentally friendly and has high calorific value. The proportion of natural gas in the global energy structure continues to increase. Coalbed methane is an unconventional natural gas with the characteristics of green transformation and energy saving. However, methane and nitrogen have very similar kinetic diameters and boiling points, which makes their separation process difficult. Therefore, the presence of nitrogen significantly affects the purification of methane and hinders the exploitation of non-natural gas.

[0003] At present, cryogenic distillation, pressure swing adsorption, temperature swing adsorption and chemical adsorption technologies are the main technologies for industrial gas separation. However, these technologies are energy intensive, require specific operating conditions, and have high operating costs. Compared with these conventional coalbed methane separation processes, membrane separation technology has the advantages of low energy consumption, mild separation conditions, simple operation, compact structure, small footprint, low operating costs, and environmental sustainability. The permeability and selectivity of the membrane are the key factors affecting the membrane separation performance. Mixed matrix membranes are a combination of porous materials and polymer substrates, showing excellent polymer processing properties, as well as adjustable pore size, high porosity and diverse structures of fillers.

[0004] For mixed matrix membranes, the intrinsic properties of porous materials play a key role in membrane performance. Among them, metal-organic framework materials with rich pore structures, structural tunability and high specific surface area show excellent gas separation performance compared with other porous materials. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problems such as the uneven carbonization of metal organic framework materials during vacuum resistance calcination and poor compatibility with the polymer matrix, which limits the application of metal organic framework material mixed matrix membranes for CH4 / N2 separation performance, and to provide a method for separating CH4 / N2 by high vacuum calcination multi-MOF mixed matrix membranes.

[0006] The technical scheme adopted by the present invention is as follows: a method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane, uniform mixing of alkaline polymer polyethylene amine with SCH-M / SCH-Z and SCH-M / SCH-U, and preparation of multi-metal organic framework mixed matrix membrane by scraping film method to achieve efficient separation of CH4 / N2; the steps are as follows:

[0007] Step S1, dissolving hexahydrate nitric acid and 2-methylimidazole in equal amounts of methanol respectively and mixing them for reaction to obtain white ZIF-8 nanoparticles;

[0008] Step S2, adding nickel nitrate hexahydrate and 2,5-dihydroxyterephthalic acid to a mixed solution of N,N-dimethylformamide, ethanol and water for reaction; dissolving zirconium chloride and aminoterephthalic acid in concentrated hydrochloric acid and N,N-dimethylformamide, and using a solvothermal method to obtain yellow-green MOF-74-Ni and white UiO-66-NH2 nanoparticles;

[0009] Step S3, using a vacuum resistance evaporation coating apparatus to perform vacuum resistance calcination on the synthesized ZIF-8, MOF-74-Ni, and UiO-66-NH2 nanoparticles to form surface carbonization hardened SCH-Z, SCH-M, and SCH-U;

[0010] Step S4, soaking the surface of the polysulfone membrane with polydimethylsiloxane with polyvinyl alcohol to prepare a hydrophilic modified MPSf membrane surface;

[0011] Step S5, mixing the basic polymer polyvinylamine with SCH-MOF (SCH-Z, SCH-M, SCH-U), and coating it on the surface of the modified MPSf membrane, and self-assembling the interface to form PVAm / 48% (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf mixed matrix membrane and PVAm / 45% (SCH-M) 0.67 (SCH-U) 0.33 / MPSf mixed matrix membrane.

[0012] Furthermore, in step S1, the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 9:10, and the ZIF-8 nanoparticles after the reaction are washed with anhydrous methanol solution for three days and placed in a vacuum oven at 60°C for 12 hours.

[0013] Furthermore, in step S2, nickel nitrate hexahydrate and 2,5-dihydroxyterephthalic acid are completely dissolved in the mixed solution by ultrasonic treatment, and then transferred to a polytetrafluoroethylene-lined high-pressure reactor, heated to 125° C. in a blast oven for reaction for 20 hours. After the reaction is completed, the mixture is washed three times with N,N-dimethylformamide and replaced with methanol, and then centrifuged in the same steps and placed in a vacuum oven for drying for 24 hours.

[0014] Further, in step S2, 0.932 g of aminoterephthalic acid and zirconium chloride were weighed out, and the aminoterephthalic acid and zirconium chloride were dissolved in 24 mL of N,N-dimethylformamide and 0.665 mL of concentrated hydrochloric acid, and immediately stirred evenly with a magnetic stirrer; then, the reaction was carried out at 220°C for 24 hours, and then the mixture was washed three times with N,N-dimethylformamide and methanol, and then dried to obtain UiO-66-NH2 nanoparticles.

[0015] Further, in step S3, about 15 mg to 20 mg of nanoparticle material is evenly placed in the groove of the tubular tungsten boat, and vacuum is evacuated in a vacuum resistance evaporation coating apparatus; when the pressure in the vacuum chamber reaches 4.7×10 -3 When 0.040 ℃ and 0.050 ℃, the evaporation power supply is turned on and the current passes through the tubular tungsten boat.

[0016] Further, in step S3, the calcination currents of MOF-74-Ni, UiO-66-NH2 and ZIF-8 are 75A (249°C), 110A (407°C) and 100A (362°C), respectively, and the calcination time is 5min, 5min and 15min, respectively; the whole process is cooled by circulating water; after the circulating water cooling process, SCH-MOF (SCH-M, SCH-U, SCH-Z) is obtained, retaining the original microporous characteristics of the metal organic framework, while introducing additional mesoporous structures and unsaturated metal sites. Having abundant metal site active sites and exposed surface atoms can improve chemical activity and increase the contact efficiency with gas molecules.

[0017] Furthermore, in step S4, the surface of the polysulfone membrane with polydimethylsiloxane is soaked with 0.025wt% polyvinyl alcohol and 50-60mL. Since polyvinyl alcohol contains abundant hydroxyl groups, polyvinyl alcohol interacts with Si-O bonds in polydimethylsiloxane to form hydrogen bonds, thereby enhancing the affinity between the polyvinyl alcohol layer and the polydimethylsiloxane layer; the membrane is completely dried at 30°C and 40% RH to obtain an MPSf membrane with a hydrophilic surface.

[0018] Further, in step S5, SCH-Z and SCH-M, SCH-M and SCH-U are mixed with 0.1 wt % PVAm aqueous solution to produce a uniform PVAm-MOF mixture.

[0019] Furthermore, in step S5, a scraper is used to evenly coat the uniformly dispersed casting solution on the MPSf membrane with a preset thickness of 400 μm; the amount of SCH-MOF added is adjusted to prepare casting solutions with different contents (such as Eq. (1)), MOF content (wt%) = (m(MOFs) / (m(MOFs)+m(PVAm)))×100% (1). PVAm is a polar polymer, and CH4 is a non-polar molecule with polar bonds. According to the principle of like-for-like, the two can be fused, and the preparation of MMMs can promote the adsorption efficiency of CH4, thereby achieving the separation effect.

[0020] Furthermore, the multi-MOF mixed matrix membrane calcined under high vacuum was used for gas separation.

[0021] Furthermore, high vacuum calcined multi-MOF mixed matrix membrane was used for CH4 / N2 gas separation.

[0022] Advantages of the present invention: (1) The present invention optimizes the heating area of ​​the vacuum device and mixes two carbonized MOF nanoparticles to add more metal sites and functional groups to improve CH4 performance and increase CH4 / N2 selectivity. MMMs prepared by blending PVAm with different SCH-M / SCH-Z and SCH-M / SCH-U ratios have good CH4 permeability and excellent CH4 / N2 selectivity, and have broad application prospects.

[0023] (2) The high vacuum calcined mixed matrix membrane for separating methane / nitrogen by multi-MOFs prepared by the present invention makes full use of high vacuum resistance calcination to carbonize MOF, solving the problem of uneven carbonization and poor compatibility of polymer matrix on the gas separation performance of MMMs. The operation is simple, the conditions are mild, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is PVAm / (SCH-M) in Example 1 0.7 (SCH-Z) 0.3 / MPSf and PVAm / (SCH-M) 0.67 (SCH-Z) 0.33 Surface SEM images, cross-sectional SEM images and AFM images of / MPSf MMMs membrane samples.

[0025] Figure 2 These are the adsorption-desorption isotherms of N2 at 77K for ZIF-8 and SCH-Z, MOF-74-Ni and SCH-M, UiO-66-NH2 and SCH-U in Example 2 (Figure (a), Figure (b), Figure (c)).

[0026] Figure 3 For Example 3, 48% ((SCH-M) 0.5 (SCH-Z) 0.5 ) loaded with MMM (a) and with 45% ((SCH-M) 0.5 (SCH-U) 0.5 ) EDS image of the loaded MMM (b).

[0027] Figure 4 These are the CH4 and N2 adsorption isotherms of ZIF-8 and SCH-Z, MOF-74-Ni and SCH-M, UiO-66-NH2 and SCH-U in Example 4 at 298K (Figure (a), Figure (b), Figure (c)). DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] A method for separating CH4 / N2 by high vacuum calcining multi-MOF mixed matrix membrane is intended to achieve effective separation of methane and nitrogen, belonging to the field of membrane separation technology.

[0030] The method used in the present invention is vacuum resistance calcination technology, which significantly improves the separation performance of CH4 / N2. Specifically, the materials used include surface carbonized and hardened ZIF-8 (SCH-Z), MOF-74-Ni (SCH-M) and UiO-66-NH2 (SCH-U). The nanoparticles treated with vacuum resistance calcination retain the microporous characteristics of MOF, while introducing additional mesoporous structures and unsaturated metal sites.

[0031] The present invention adopts a uniform mixture of alkaline polymer polyvinylamine with SCH-M / SCH-Z and SCH-M / SCH-U, and adopts a scraping film method to prepare a multi-metal organic framework mixed matrix membrane. In the experiment, when the pressure is 0.1MPa and the filler filling amount is 48%, PVAm / (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf MMM showed excellent CH4 / N2 separation performance, with a CH4 permeability of 2888.48GPU and a selectivity of 4.38. On the other hand, when the filling amount was 45%, PVAm / (SCH-M) 0.67 (SCH-U) 0.33 The ideal CH4 / N2 selectivity and CH4 permeability of / MPSf MMM are 5.57 and 2263.94 GPU respectively. The present invention provides a new idea for introducing multi-radical nanoparticles into metal matrix composite materials to optimize gas separation performance.

[0032] The innovation of the present invention is that MOF materials have poor compatibility with polymers. The multi-MOF blend after vacuum resistance calcination treatment introduces additional mesoporous structures and unsaturated metal sites. The edge effect and state can improve chemical activity and increase the contact efficiency with gas molecules. PVAm is a polar polymer, and CH4 is a non-polar molecule with polar bonds. According to the principle of similar compatibility, the two can be fused. The alkaline polymer polyvinylamine is evenly mixed with SCH-M / SCH-Z and SCH-M / SCH-U, and the multi-metal organic framework mixed matrix membrane is prepared by the scraping film method to promote the adsorption rate of CH4, thereby obtaining a good CH4 / N2 separation effect.

[0033] Embodiment 1:

[0034] (1) SCH-Z (100A (362°C)), SCH-M (75A (249°C)), and SCH-U (110A (407°C)) were prepared by vacuum resistance calcination of ZIF-8, MOF-74-Ni, and UiO-66-NH2. The calcination time was 2 h, and the whole process was cooled by circulating water.

[0035] (2) 0.025 wt % polyvinyl alcohol was used to coat the surface of polysulfone with PDMS with an average pore size of 20-50 nm to prepare a hydrophilic modified MPSf membrane surface.

[0036] (3) 0.1 wt% of basic polymer polyvinyl amine and ((SCH-M) 0.7 (SCH-Z) 0.3 )、((SCH-M) 0.67 (SCH-U) 0.33 ) is prepared into a uniform casting solution

[0037] (4) Use a scraper to apply the uniformly prepared casting solution on the surface of the hydrophilic modified MPSf membrane to form PVAm / (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf and PVAm / (SCH-M) 0.67 (SCH-Z) 0.33 / MPSf MMMs.

[0038] Figure 1 It shows that PVAm / (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf membrane surface and PVAm / (SCH-M) 0.67 (SCH-Z) 0.33 / MPSf MMMs film surface, confirming that the nanoparticles were successfully doped and evenly dispersed in PVAm, and the MMMs film surface was dense and uniform. Atomic force microscopy further proved that MOF promoted the interface contact with the polymer. In addition, Figure 1 It is shown that the cross-sectional thicknesses of the MMMs are ∼602.8 nm and ∼580.6 nm, respectively, indicating that there is no gap between the MMMs and the support layer and the interface bonding is good.

[0039] Embodiment 2:

[0040] (1) SCH-Z (100A (362°C), SCH-M (75A (249°C)), and SCH-U (110 (407°C)) were prepared by vacuum resistance calcination of ZIF-8, MOF-74-Ni, and UiO-66-NH2. The calcination time was 3 h, and the whole process was cooled by circulating water.

[0041] (2) 0.75 wt % polyvinyl alcohol was used to coat the surface of polysulfone with PDMS with an average pore size of 20-50 nm to prepare a hydrophilic modified MPSf membrane surface.

[0042] (3) 0.5 wt% of basic polymer polyvinyl amine and ((SCH-M) 0.7 (SCH-Z) 0.3 )、((SCH-M) 0.67 (SCH-U) 0.33 ) is prepared into a uniform casting solution

[0043] (4) Use a scraper to apply the uniformly prepared casting solution on the surface of the hydrophilic modified MPSf membrane to form PVAm / (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf and PVAm / (SCH-M) 0.67 (SCH-Z) 0.33 / MPSf MMMs.

[0044] Figure 2 The N2 adsorption-desorption isotherms of the nanoparticles at 77K are shown. The vacuum calcination treatment of ZIF-8, MOF 74-Ni and UiO-66-NH2 resulted in a decrease in specific surface area and specific volume, indicating that the vacuum treatment led to the collapse of the SCH-Z, SCH-M and SCH-U surfaces and the formation of micro-defects. Pore hysteresis loops were observed in the isotherms, and the mesopore volume of the treated nanoparticles increased accordingly, and combined with the analysis of the pore size distribution, it was shown that etching had occurred and a mesoporous structure was generated in the skeleton. PVAm / (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf and PVAm / (SCH-M) 0.67 (SCH-Z) 0.33 The nanoparticles of / MPSf MMMs after vacuum calcination have a multi-level pore structure and abundant metal sites, which are beneficial to enhance the compatibility with the PVAm matrix and the film-forming properties.

[0045] Figure 2It shows that the FTIR spectrum of nanoparticles is used to characterize the components of nanoparticles and determine the functional groups involved. It can be seen from the figure that there is no significant change in the peak position of the SCH-Z, SCH-M, and SCH-U spectra, and the peak intensity of the nanoparticles after vacuum calcination is reduced. It shows that some Zn-N bonds, Ni-O and Zr-O bonds are broken, resulting in unsaturated sites and surface atoms. It is beneficial to improve chemical activity and increase the contact rate with gas, thereby achieving separation.

[0046] Embodiment 3:

[0047] (1) SCH-Z (100A (362°C)), SCH-M (75A (249°C)), and SCH-U (110A (407°C)) were prepared by vacuum resistance calcination of ZIF-8, MOF-74-Ni, and UiO-66-NH2. The calcination time was 2 h, and the whole process was cooled by circulating water.

[0048] (2) 0.025 wt % polyvinyl alcohol was used to coat the surface of polysulfone with PDMS with an average pore size of 20-50 nm to prepare a hydrophilic modified MPSf membrane surface.

[0049] (3) 1.5 wt% of basic polymer polyvinyl amine and ((SCH-M) 0.5 (SCH-Z) 0.5 )、((SCH-M) 0.5 (SCH-U) 0.5 ) is prepared into a uniform casting solution

[0050] (4) Use a scraper to apply the uniformly prepared casting solution on the surface of the hydrophilic modified MPSf membrane to form PVAm / (SCH-M) 0.5 (SCH-Z) 0.5 / MPSf and PVAm / (SCH-M) 0.5 (SCH-U) 0.5 / MPSf MMMs.

[0051] Figure 3 Indicates PVAm / (SCH-M) 0.5 (SCH-Z) 0.5 / MPSf and PVAm / (SCH-M) 0.5 (SCH-U) 0.5 The SEM images and EDS of the / MPSfMMMs membrane surface confirmed that the multi-MOF mixed matrix membrane was successfully prepared by the scraping method and that the multi-MOF could be uniformly dispersed in PVAm, and the membrane surface of the MMMS was dense and uniform.

[0052] Embodiment 4:

[0053] (1) SCH-Z (110A (407°C)), SCH-M (85A (294°C)), and SCH-U (110 (407°C)) were prepared by vacuum resistance calcination of ZIF-8, MOF-74-Ni, and UiO-66-NH2. The calcination current was adjusted. The calcination time was 2 h, and the whole process was cooled by circulating water.

[0054] (2) 0.025 wt % polyvinyl alcohol was used to coat the surface of polysulfone with PDMS with an average pore size of 20-50 nm to prepare a hydrophilic modified MPSf membrane surface.

[0055] (3) 0.1 wt% of basic polymer polyvinyl amine and ((SCH-M) 0.7 (SCH-Z) 0.3 )、((SCH-M) 0.67 (SCH-U) 0.33 ) is prepared into a uniform casting solution

[0056] (4) Use a scraper to apply the uniformly prepared casting solution on the surface of the hydrophilic modified MPSf membrane to form PVAm / (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf and PVAm / (SCH-M) 0.67 (SCH-Z) 0.33 / MPSf MMMs membrane.

[0057] Figure 4 Indicates PVAm / (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf and PVAm / (SCH-M) 0.67 (SCH-Z) 0.33 The adsorption isotherms of / MPSfMMMs for CH4 and N2 show that SCH-Z, SCH-M and SCH-U still have adsorption capacity, and the nanoparticles still have certain microporosity. The degree of reduction in adsorption performance of CH4 is lower than that of N2. This shows that during the heat treatment under vacuum conditions, rich metal sites and highly mesoporous porous structures can be obtained. Such a structure can provide additional transmission channels and action sites for gas molecules, which can improve CH4 adsorption and selectivity.

Claims

1. A method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membranes, characterized in that: Basic polymer polyethylene amine was uniformly mixed with SCH-M / SCH-Z and SCH-M / SCH-U, and a multi-metal organic framework mixed matrix membrane was prepared by a scraping film method to achieve efficient separation of CH4 / N2; the steps are as follows: Step S1, dissolving hexahydrate nitric acid and 2-methylimidazole in equal amounts of methanol respectively and mixing them for reaction to obtain white ZIF-8 nanoparticles; Step S2, adding nickel nitrate hexahydrate and 2,5-dihydroxyterephthalic acid to a mixed solution of N,N-dimethylformamide, ethanol and water for reaction; dissolving zirconium chloride and aminoterephthalic acid in concentrated hydrochloric acid and N,N-dimethylformamide, and using a solvothermal method to obtain yellow-green MOF-74-Ni and white UiO-66-NH2 nanoparticles; Step S3, using a vacuum resistance evaporation coating apparatus to perform vacuum resistance calcination on the synthesized ZIF-8, MOF-74-Ni, and UiO-66-NH2 nanoparticles to form surface carbonization hardened SCH-Z, SCH-M, and SCH-U; Step S4, soaking the surface of the polysulfone membrane with polydimethylsiloxane with polyvinyl alcohol to prepare a hydrophilic modified MPSf membrane surface; Step S5, mixing the basic polymer polyvinylamine with SCH-MOF (SCH-Z, SCH-M, SCH-U), and coating it on the surface of the modified MPSf membrane, and self-assembling the interface to form PVAm / 48% (SCH-M) 0.7 (SCH-Z) 0.3 / MPSf mixed matrix membrane and PVAm / 45% (SCH-M) 0.67 (SCH-U) 0.33 / MPSf mixed matrix membrane.

2. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 1, characterized in that: In step S1, the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 9:

10. The ZIF-8 nanoparticles after the reaction are washed with anhydrous methanol solution for three days and placed in a vacuum oven at 60° C. to dry for 12 h.

3. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 2, characterized in that: In step S2, nickel nitrate hexahydrate and 2,5-dihydroxyterephthalic acid are completely dissolved in the mixed solution by ultrasonic treatment, and then transferred to a polytetrafluoroethylene-lined high-pressure reactor, heated to 125° C. in a blast oven for reaction for 20 hours. After the reaction is completed, the mixture is washed three times with N,N-dimethylformamide and replaced with methanol, and then centrifuged in the same steps and placed in a vacuum oven for drying for 24 hours.

4. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 3, characterized in that: In step S2, 0.932 g of aminoterephthalic acid and zirconium chloride were weighed out, dissolved in 24 mL of N,N-dimethylformamide and 0.665 mL of concentrated hydrochloric acid, and immediately stirred evenly with a magnetic stirrer; then, the reaction was carried out at 220°C for 24 hours, after which the mixture was washed three times with N,N-dimethylformamide and methanol, and then dried to obtain UiO-66-NH2 nanoparticles.

5. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 4, characterized in that: In step S3, about 15 mg to 20 mg of nanoparticle material is evenly placed in the groove of the tubular tungsten boat, and vacuum is evacuated in a vacuum resistance evaporation coating apparatus; when the pressure in the vacuum chamber reaches 4.7×10 -3 When 0.040 ℃ and 0.050 ℃, the evaporation power supply is turned on and the current passes through the tubular tungsten boat.

6. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 5, characterized in that: In step S3, the calcination currents of MOF-74-Ni, UiO-66-NH2 and ZIF-8 are 75A (249°C), 110A (407°C) and 100A (362°C), respectively, and the calcination time is 5min, 5min and 15min, respectively; the whole process is cooled by circulating water; after the circulating water cooling process, SCH-MOF (SCH-M, SCH-U, SCH-Z) is obtained, retaining the original microporous characteristics of the metal organic framework, while introducing additional mesoporous structures and unsaturated metal sites. Having abundant metal site active sites and exposed surface atoms can improve chemical activity and increase the contact efficiency with gas molecules.

7. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 6, characterized in that: In step S4, the surface of the polysulfone membrane with polydimethylsiloxane is soaked with 50-60 mL of 0.025 wt % polyvinyl alcohol. Since polyvinyl alcohol contains abundant hydroxyl groups, polyvinyl alcohol interacts with Si-O bonds in polydimethylsiloxane to form hydrogen bonds, thereby enhancing the affinity between the polyvinyl alcohol layer and the polydimethylsiloxane layer. After complete drying at 30 °C and 40% RH, the MPSf membrane with a hydrophilic surface was obtained.

8. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 7, characterized in that: In step S5, SCH-Z and SCH-M, SCH-M and SCH-U are mixed with 0.1 wt% PVAm aqueous solution to produce a uniform PVAm-MOF mixture.

9. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 8, characterized in that: In step S5, a scraper is used to evenly coat the uniformly dispersed casting solution on the MPSf membrane with a preset thickness of 400 μm; the amount of SCH-MOF added is adjusted to prepare casting solutions with different contents (such as Eq. (1)), MOF content (wt%) = (m(MOFs) / (m(MOFs)+m(PVAm)))×100% (1). PVAm is a polar polymer, and CH4 is a non-polar molecule with polar bonds. According to the principle of like-for-like, the two can be fused, and the preparation of MMMs can promote the adsorption efficiency of CH4, thereby achieving the separation effect.

10. The method for separating CH4 / N2 by high vacuum calcination of multi-MOF mixed matrix membrane according to claim 9, characterized in that: High vacuum calcined multi-MOF mixed matrix membranes for gas separation.

Citation Information

Patent Citations

  • Metal-organic framework mixed matrix membrane as well as preparation method and application thereof

    CN114642975A

  • High-performance anti-aging c-PIM / UiO cross-linked membrane as well as preparation method and application thereof

    CN118634668A

  • Pd-coated MOF gel mixed matrix membrane for improving hydrogen transmission and separation efficiency as well as preparation method and application of Pd-coated MOF gel mixed matrix membrane

    CN118807499A

  • Method for making porous filter membranes

    WO2021104937A1